Rancang Bangun Aplikasi Absensi Siswa dengan Fitur Monitoring Orang Tua Menggunakan Metode Agile - Randi Praditiya; Dwi Sartika Simatupang (Riviera Publishing, 2025)
The conventional student attendance process at Rancagong 1 Elementary School still relies on manual recording in class journals, which is considered inefficient and prone to errors. The main problem is the delay in information received by parents regarding their children's attendance, making direct monitoring difficult. This research aims to design and build an Android-based student attendance application with parent monitoring features using the Agile method. The Agile methodology was chosen because it enables iterative development with planning, implementation, testing, and evaluation stages. The resulting application has four main access rights: admin, teacher, student, and parent. Black Box Testing results confirmed that all functionalities work according to the design. Evaluation using the System Usability Scale (SUS) with 30 respondents yielded an average score of 87.58, indicating excellent usability. This application proves effective in digitalizing attendance processes, improving teacher efficiency, and strengthening communication with parents through real-time monitoring features.